Decoding the Nature of Dark Matter at Current and Future Experiments - Belyaev, Alexander (Frontiers in Physics, 2019)
Determination of the nature of Dark Matter (DM) is one of the most fundamental problems of particle physics and cosmology. If DM is light enough and interacts with Standard Model particles directly or via some mediators with a strength beyond the gravitational one, it can be probed at particle accelerators or in complementary direct and indirect DM searches in non-collider experiments. In the absence of such signals at present we can prepare ourselves for its discovery and identification. Generic signature from DM produced in particles collisions is missing transverse energy, MET, originating from DM particles escaping detector. Using effective field theory approach one can show that, depending on the structure and DM spin, effective operators have different MET distributions. This provides potential to distinguish certain classes of effective field theory (EFT) operators and related spin of DM at the LHC. This observation can be directly applied to theories beyond EFT paradigm as we demonstrate for Supersymmetry and inert two Higgs doublet model (i2HDM) as two examples. At the same time direct and indirect DM searches strongly complement collider searches for DM with large masses and pointing that collider and non-collider DM searches have unique power to probe the nature of Dark Matter. We also highlight prospects of new collider signature from DM such as disappearing charge tracks which are characteristic for wide class of DM theories. Finally, we advocate the importance of the joint framework which would join efforts of HEP community and allow to effectively identify the underlying theory of DM.